A game-based learning strategy for learning Jawi on Sony PSP (playstation portable) / Liza Dariman - Dariman, Liza (2010)
Jawi is a subject that is thought to the preschoolers as a basic before they learn Arabic language. The preschoolers learn about the Jawi alphabets and simple word. Sony PlayStation Portable or Sony PSP is a handheld game console released and manufactured by Sony Computer Entertainment. A game-based learning strategy for Jawi learning on Sony PSP is a research project that focuses on the user requirement of the topic. This research takes consideration all issues related to the game-based learning as a method of learning, Jawi subject for preschoolers, and Sony PSP which is the game console that is used for learning. The scope of this project is to purpose a game-based learning strategy for learning Jawi on Sony PSP based on the requirements of Jawi learning for the preschoolers and the Sony PSP features. Even though courseware is used for learning, this research purpose a new approach using portable game console, Sony PSP to make learning process more interactive and fun. Besides, other than computer game courseware, Sony PSP offers portability for its users in term of size and weight. The method of this research is to identify and analyze the information gathered from the primary data collection which is interview and secondary data collection which is review on the literature. Then the research will purpose a game-based learning strategy for learning Jawi on Sony PSP based on the analysis.